Detection of loci under selection in Apis mellifera iberiensis as compared with two frequentist methods - Chávez-Galarza, Julio (2012)
Genome scans with many genetic markers provide the opportunity to investigate local adaptation in natural populations and identify candidate genes under selection. The recent advent of high-throughput Single Nucleotide Polymorphism (SNP) genotyping technologies have opened new perspective of research and these markers are commonly observed in functional genes making them ideal markers to study adaptive molecular variation. This approach has become commonly employed in ecological and population genetics studies to detect outlier loci that are putatively under selection. Herein, we show a preliminary exploration of a gnome scan to detect signatures of selection on the Iberian honey bee genome The objective of this study was to determine loci under selection of A m. iberiensis by using SNPs. Over 711 individuals were sampled in the lberian Peninsula across three Latitudinal transects and then genotyped for 1536 SNPs using the Golden Gate Assay of Illumina. Loci under selection were identified by two frequentist methods: Fdist, implemented in LOSITAN, and BAYESCAN. There were identified 22 loci under selection by BAYESCAN and 12 Loci by LOSITAN, being 10 Loci detected by both methods. The SNPs under selection were located in linkage group I1 4, 6, 7, 8, 9, 10, 11 , 12, 13 and 15 from honey bee genome and may be related to genes with diverse functions as hormonal, nervous, development, cell signaling and some unknown.